THE CULTURE OF LEGAL ENTREPRENEURSHIP IN PUBLIC UNIVERSITIES FROM COACHING - Timbira Dias dos Santos, Fredson (Revista Gênero e Interdisciplinaridade, 2023)
This article explores the development of legal entrepreneurship culture in public universities through coaching. While the relationship between public universities and productive sectors in Brazil is limited, in the United States, this culture is more pronounced, having a global influence since the 20th century. Universities are hubs for knowledge production and professional advancement. However, depending on a country’s political perspective, academic entrepreneurship can either be readily embraced or face cultural barriers. For instance, while the U.S. boasts a strong tradition of academic entrepreneurship, Brazil, despite progress, still finds this culture hindered by political and economic factors. Particularly in Brazil, debates about the state’s role in the economy, especially education, are exacerbated by ongoing political and economic crises. This context raises questions about promoting entrepreneurship, specifically in the legal field, within public universities. How can coaching assist in this endeavor, bridging the gap between academia and productive sectors? This paper argues that entrepreneurship, prevalent in the business world, is vital in the academic setting, especially in the legal domain traditionally oriented towards public service. A further rationale for this study is the rising global significance of coaching and its benefits for human and institutional development. The article employs the inductive method by Francis Bacon, examining how coaching can cultivate an entrepreneurial spirit in academia, specifically at the State University of Bahia in Itaberaba.